A Common Currency Peg in East Asia? Perspectives from Western Europe - Chow, Hwee Kwan (Institutional Knowledge at Singapore Management University, 2003)
In this paper we investigate the feasibility of a common currency peg in East Asia from the perspective of Western European countries. We findthat domestic outputs of East Asian countries are strongly influencedby country-specific shocks while regional shocks are far more important in European countries that have joinedthe Economic andMonetary Union. The results are robust to various changes in specifications of the model. They suggest that East Asian countries are structurally different from each other and thus more likely to be subject to asymmetric shocks. Basedon optimum currency area grounds, a common currency peg in East Asia wouldbe more costly anddifficult to sustain